Harapan dan Kenyataan Penerapan âKawasan Tanpa Rokok (KTR)â di Lingkungan Kampus Universitas Udayana Denpasar - Kamajaya, Gede; Nugroho, Wahyu Budi; Tamim, Imron Hadi (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2017)
This research attempts to examine the effectiveness of the areas without smokeables âKawasan Tanpa Rokokâ(KTR) policy in Udayana University, Denpasar which was implemented at about one year (June 2015-June 2016). Furthermore, this research aims to emphasize the rationality of the smokers which are continuing to smoke although the KTR signs was put in the Udayana University areas. To accent the private and personal rationality, the phenomenology method which focus on subjective actor (the smokers) was used in this research. This method is a qualitative method and purpose to collect the deeper data to expound the personal reasons of the smokers who always smoke continuously in KTR areas. From the result of the research, there were some problems that made the KTR policy was not effective in Udayana University areas. First, there was no clear sanction for the smokers; Second, the lecture and the university employee did not show the good instance to comply with the KTR policy; Third, a cigarette was sell openly in University store (Waserda); Fourth, there was no smoking areas for the smokers in Udayana University, Denpasar.Â